Profile of Storage System of LASA Drug Services in a Pharmacy, Besuki District, Situbondo Regency - Hakim, Abdul; Maulina, Novia; Syahrir, Ach; Bayyinah, Qoyyimatul (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v1i0.1452, 2021)
The development of drug production is relatively rapid, causing several drugs that have almost the same shape, name, and packaging. This can cause medication errors in the form of errors in administering drugs to patients. Drugs that are nearly the same shape and name are known as LASA (Look Alike Sound Alike) drugs. This study aimed to determine the profile of the LASA drug storage and service system at pharmacies in Besuki District, Situbondo Regency. This research includes qualitative research through in-depth interviews and direct observation. The sample used in this study is a saturated sample. The results showed that the LASA drug storage system in pharmacies throughout Besuki District, Situbondo Regency only implemented a system of giving the distance between drugs one and other drugs, while other provisions for storing Lasa drugs were not carried out. The LASA drug service system is carried out by conducting double checks, memorizing various LASA drugs, and contacting doctors to clarify prescriptions for LASA drugs. Based on these results, it can be concluded that pharmacies in Besuki District, Situbondo Regency, do not meet the criteria in the LASA drug storage system. Meanwhile, in the LASA drug service system, pharmacies throughout Besuki District, Situbondo Regency have met the requirements for LASA drug services.